Exploring socially responsible consumption intentions for gender-responsive cacao value chains in the Philippines - Lapitan, Aileen V.; Predo, Canesio; Lopez, Mitchiko; Anastacio, Nico Jayson; Aranas, Mia Barbara; Faylon, Rassel; Flores, Emmanuel (University of the Philippines, 2023)
In the Philippines’ cacao sector, women and men take on various roles in the production and creation of values for the commodity. As gender-based inequalities are rife in agricultural value chains, addressing equity issues is justified in terms of business, social justice or development cases. The social justice argument for gender equality as a desired outcome is widely accepted by the development practitioners and scholars. On the other hand, the development case relies on the mutually supportive links between social justice and the business case. This paper focuses on the role of gender in the business case that goes beyond the productivity benefits of encouraging women’s participation and removal of gender-based barriers to production and processing. It explores the potential of tapping into the buying power of consumers who are willing to place premium value on socially desirable and gender-responsive actions in the cacao value chain. Using data gathered through an online survey in emerging markets for Philippine chocolate and a series of focus group discussions, the study examined intentions for socially responsible consumption among chocolate consumers. Findings show some opportunities and difficulties in expanding the scope of social certifications while bolstering the commercial case for gender equality for social justice. Policy implications and recommendations are discussed in the paper.